Halal economic: challenges and emerging opportunities in Malaysia / Nadzirah Mohd Fauzi ... [et al.] - Mohd Fauzi, Nadzirah; Hashim, Nur Iman; Ab Rahman, Mohd Fadhli; Wan Hassin, Wan Suraya; Shah Shahar, Wan Shahzlinda (Center for Islamic Philantrophy & Social Finance (CIPSF), 2020)
The purpose of the paper is to investigate the challenges and opportunities for halal industries in Malaysia. Since the market for certified Halal products is developing robustly, both domestically and internationally and Malaysia has become the leader and centre of reference for the world. This research builds on existing research published in the Munich Personal RePEc Archive on challenges and opportunities in halal industry. In addition to an extensive literature review, four segment of halal categories were discussed in order to discover the challenges and opportunities with regards to halal industry in Malaysia. The results show that the future market demands and the competitive opportunities related to halal industry are the main motivators for Malaysia to undertaken the significant initiatives across regulation, trade and industry support to strengthen the status as a Halal hub in the trade-driven of Islamic economy. The early adopters for each of halal segments face several challenges such as ambiguous halal guidelines, lack of international halal certification, lack of collaboration among governing agencies (i.e. Jabatan Kemajuan Islam Malaysia (JAKIM) and Halal Industry Development Corporation), a lack of cost-effective standards and a general misunderstanding of halal practices. The findings of the present study may help government policy makers recognise the issues that should be addressed in motivating industries players to adopt halal practices. This study contributes to the advancement of knowledge on the challenges and opportunities of adopting halal certificate in Malaysia.